Discrete element method study on hopper discharge behaviors of binary mixtures of nonspherical particles - Zhao, Ya (2021)
This study is aimed at unveiling the influence of binary mixtures of nonspherical particles on hopper discharge behavior, which remains poorly understood. The discrete element method (DEM) is employed to simulate seven particle types with aspect ratios between 0 and 2 (namely, a sphere, two ellipsoids, two cylinders, and two cuboids) with the same volume. Seven monodisperse systems and twelve binary-shape mixtures are assessed. For the monodisperse systems, particle shape is the dominant factor dictating discharge rate, compared to other factors like aspect ratio, preferential orientation, and packing. Regarding the binary-shape mixtures, the discharge rates are similar for all twelve mixtures, reflecting a surprising lack of shape effects, which in turn means the negligible impact of solid volume fraction, aspect ratio, and segregation extent. Moreover, collision force is generally negatively correlated with discharge rate.